Internet in a nutshell : a desktop quick reference - Quercia, Valerie (A nutshell handbook, 1997)
Internet in a Nutshell is a quick-moving guide to the Internet that goes beyond the "hype" and right to the heart of the matter: how to get the Internet to work for you. This is a second generation Internet book for readers who have already taken a spin around the Internet and now want to learn the shortcuts. This is the Internet book for readers who don't think they need a book to use the Internet. The book includes tips and reference for Netscape Communicator 4.01 and Internet Explorer 3.02; a "living glossary" to the Internet, which is a fast-moving introduction for the impatient; a quick-reference on browsing the Web, reading email, and news; comparisons of the strengths of each of the most popular search engines and other unique services provided on the Internet; detailed coverage of transferring files over the Internet using your browser, FTP, or email; and coverage of web authoring, with topics ranging from basic HTML to creating animated GIFs and using JavaScript.